Caracterización forestal existente en un bosque secundario del centro de producción e investigación Pabloyacu, para su manejo integral - Villacís Del Castillo, Susana (2010)
The present investigation work, presents information obtained during the months of June to December of the 2009, carried out with the purpose of giving to know the importance of carrying out a characterization florística in a secondary forest, this way they took better decisions for the handling of the area, since a secondary forest provides us of many benefits. The purpose of this work, is to diminish the pressure toward the primary forests, so that not you talen and that sosteniblemente the secondary forests are managed, since he/she offers us a without number of environmental services, because they are directly related with four big areas ofworld concem: climatic changes, conservation ofthe biodiversity, conservation ofthe genetic resources and forest sustainable production. To give an appropriate handling to the forest, it is needed to characterize the existent flora, to carry out the biometric inventory of the species, to determine the index of value of importance and index of wealth. With these obtained data the future of the forest was determined, this way it will be known about its current situation. The composition florística in each type of vegetable covering, in di cates that the secondary youngest forests are simpler in the conformation of forest species, increasing its complexity to bigger age ofthe evaluated parcel. Coinciding with that mentioned by Lamprecht (1990) that the young forests have a simpler structure and they are much poorer in species that the primary forests of the same atmosphere. The lndex of Value Importance. lVI, of the parcels of the evaluated forest, shows the conformation of associations of species forest pioneers with ecological bigger weight, for its presence, abundance, dominancia and frequency; species of quick growth and intolerant to the shade.